Alohomara / Aini Qamariah Mohd Yusof … [et al.] - Mohd Yusof, Aini Qamariah; Osman, Shahariah; Idrus, Syukuriah; Samsuddin, Nurshamimah; Mohd Nor, Maliza (Division of Research and Industry Linkages, 2017)
Autism is considered a developmental disorder of unknown etiology with diverse behavioral characteristics; it is a long life development where the kids who face with this problem might having a difficulty include delay in social life development, problem in communication and slow progress in motor skill development. Alohomara is a magic box specially designed for kids with autism. Inside this magic box are five different games that help to develop important skills among , autism kids. The name Alohomara is taken from ancient magic spell for unlocking ' any charm. For that, all games in this box have their own unique way to open or unlock it. The first game is called Colovaria, is a color change charm that develop focus and attention. The second game is called Alakazam, is a sensory mat that focus on calming sensory integration. The third game is Aguamenti, a gel squeezy pad that covers motor skill and development. The fourth game is Diminuendo, a combination of shapes puzzle for brain development and the last games is called Ferula, a flash card that helps autism kids to communicate better and it covers social and communication skills. This magic box is actually a therapy box that includes most of the skills needed by autism kids. It is handy and easy to carry anywhere and beneficial to develop skills needed by autism kids.